The effect of cultural factors on the design and acceptance of assessment centre practices in Malaysian public sector - Mohd Hanafiah, Ahmad (2018)
The proliferation of assessment centre (AC) around the world has raised questions about their application in specific countries. Although a number of studies have found that differences in cultural settings across countries may have an impact on human resource practices and strategies, very little attention has been given specifically to AC. As the AC approach has also been used in developing countries such as Malaysia, it is important to understand how these factors in different cultural settings may influence the implementation of AC and how this might differ from its implementation in more developed nations. Using the model of cultural fit and organisational justice theory, this study aims to explore how the national culture may influence the design and implementation of assessment centre in Malaysian public sectors. This exploratory study involves two stages of data collection. The respondents for the first study (semi-structured interview) are personnel who have had experience as developer/assessors, and also those who have had experience as participants, in AC in various ministries in Malaysia. The first study aims to explore how assessors and participants perceive the design, scoring methods, and feedback associated with traditional approach dimension-based assessment centre and alternative approach task-based assessment centre and how culture influence the process. For the second study (survey questionnaires), the respondents are from those who have had experience as participants. In total, a survey of 405 respondents was successfully carried out and 381 useful feedbacks were analysed. This second study utilises organisational justice theory in exploring participants’ reactions to the fairness of AC design, implementation and outcomes. A total of thirteen hypotheses have been put forward to test the relationships amongst the culture values, distributive justice latent, three categories under procedural justice, and outcome after attending AC. Structural Equation Modelling (SEM) with SmartPLS software using Partial Least Squares (PLS) estimation is used for modelling analysis. Findings from the first study showed that Malaysia is a society that put emphasis on working in group, and accept the importance of power distance, and rely on high communication context. These socio-cultural findings reflect the internal work culture which focus more on working in group, maintaining harmony, and respect to seniority in decision-making process. Meanwhile, findings for study two showed that collectivism and relationship preferences as the most significant cultural variable in influencing reaction on fairness of AC. In addition, this study also showed positive outcome related to attitude, affect and recommendation towards AC. Interestingly, this study also revealed that the relationship of power distance and preference of hierarchy onto other variables in this study is not significant, therefore, it provides a new perspective on the relationship of cultural values and management practices in this millennium. This research also has closed the gap by highlighting the practice, acceptance and outcome from attending AC in Malaysian public sector from holistic view which include assessors, participants and module developers.